55 Life experiences associated with change in adult perpetration of physical intimate partner violence. (19th September 2017) - Lyons, Vivian; Cohen-Cline, Hannah; Rowhani-Rahbar, Ali
Abstract : Statement of purpose: Few interventions have demonstrated significant reduction in intimate partner violence (IPV) perpetration, and little is known about differences between individuals who begin or discontinue IPV perpetration and those that perpetrate IPV throughout adulthood. We aimed to examine if change in financial instability and substance use are associated with change in physical IPV perpetration. Approach: In 2016, a probability sample of 10, 000 Medicaid enrollees in Oregon were surveyed on life-course experiences (response proportion=24%).To assess change in IPV perpetration from 19–30 years to 31+years of age, we restricted our study to 1883 respondents aged >31 years. Financial stability, substance use and physical IPV perpetration were assessed separately for ages 19–30 and 30+. Multinomial logistic regression was used to assess the effect of increasing financial instability and substance use cessation on physical IPV perpetration, adjusting for history of child abuse, bullying, social support and age. Results: Of the 20% of survey participants who endorsed physical IPV perpetration, 34% (95% CI: 24%–47%) perpetrated IPV both before and after age 30 (persisters), 25% (15%–38%) began IPV perpetration after the age of 30 (late-onsetters) and 41% (29%–54%) discontinued IPV perpetration (desisters). Among all perpetrators, 57% (44%–69%) also experienced physical IPV. Compared to persisters, both late-onsetters (OR:11.2, 95% CI: 3.3–38.1) and desisters (OR:5.7, 95% CI:1.9–17.5) were more likely to have increased financial instability after age 30. Desisters were more likely to report substance use cessation after age 30 when compared to persisters (OR:11.9, 95% CI:3.2–43.4), unlike late onsetters (OR:0.3, 95% CI: 0.1–1.4). Conclusion: Findings indicate increasing financial instability is associated with change in IPV perpetration while decreasing substance use is associated with desisting IPV perpetration. Results also suggest potential bi-directionality of physical IPV. Significance: Understanding life-course experiences associated with change in IPV perpetration could support tailored IPV perpetration interventions.